How do Millennial Parents Internalize Islamic Values in Their Early Childhood in the Digital Era? - Muhammad Darwis Dasopang; Azmil Hasan Lubis; Helmi Rostiana Dasopang (STAI Hubbulwathan Duri, 2022)
The development of technology is currently very rapid, influencing almost all aspects of life. With these technological developments, millennial parents must be able to adjust how to internalize Islamic values in children in the family environment. This study aims to analyze the role of millennial parents in internalizing Islamic values for early childhood in the digital era as it is today. This study uses a qualitative approach with descriptive qualitative research. The informants of this study were millennial parents who had ten children aged 4-6 years. Determination of informants is done by purposive random sampling technique. The data of this study were collected by means of virtual interviews. The data obtained were then analyzed by data triangulation techniques. The results showed that the role of millennial parents in internalizing children's Islamic values in the digital era was the Maghrib Mengaji program, optimizing the youtube kids application, using Islamic storybooks, singing Islamic songs, and optimizing animation videos for learning to pray. These five roles help internalize the Islamic values of early childhood in the digital era.